HUBUNGAN STATUS GIZI IBU SAAT HAMIL DENGAN KATEGORI STUNTING PADA BALITA DI PUSKESMAS TANJUNG HALOBAN - GUSTIANSYAH, EVAN; DAMAYANTY, AMELIA EKA (JURNAL ILMIAH MAKSITEK, 2024)
The nutritional status of pregnant women is one of the factors that cause stunting. Mothers who experience poor nutritional status can be at risk of giving birth to babies with low birth weight so that children are at risk of stunting in the future. Objective: to analyze the relationship between maternal nutritional status during pregnancy and the category of stunting in children under five in the Tanjung Haloban Health Center working area. Methods: Cross sectional research design with a quantitative approach using a total sampling of 47 mothers who have stunting toddlers. Data were collected using questionnaire sheets and observations using MCH books and z-score tables. The results: most of the mothers experienced good nutritional status during pregnancy, namely LILA > 23.5 with stunting in the short category of 27 (57.4%) and LILA < 23.5 with stunting in the very short category of 8 (17%). Bivariate analysis of the nutritional status of mothers during pregnancy with stunting category using fisher exact test showed with ρ=0.012. Conclusion: there is a relationship between maternal nutritional status during pregnancy and the category of stunting in children under five at the Tanjung Haloban Public Health Center.